Short-term effects of social encouragement on exercise behavior: insights from China's Wanbu network. (July 2017) - Wang, Liuan; Guo, Xitong; Wu, Tianshi; Lv, Lucheng; Zhang, Zhiwei
Abstract: Objectives: The objective is to explore the short-term effects of social encouragement on exercise behavior in China. Study design: A longitudinal observational study. Methods: We collected longitudinal data on exercise and social interactions through public access to the Wanbu network, a large Chinese social network designed to encourage people to walk more. Our data set consisted of 5010 subjects who participated in the network between March 14, 2014, and September 4, 2015, and had at least one social interaction recorded. The data were analyzed using linear regression models relating the number of steps (NS) walked per day to the number of comments (NC), number of thumbs-up (NT), and number of posts (NP) received on the previous day, while adjusting for day of week, quarter of year, and a fixed or random subject effect, with or without a lag term (NS on the previous day) to account for serial correlation. Results: We found that all three social interactions have positive effects on the next day's exercise level. The estimated effect sizes can be ordered as NT > NC > NP for each of the four models considered. The results also indicate that the participants walked less in the first quarter than in the other three quarters and more on weekdays than on weekends, with Monday being the most active day of a week. Conclusion: Social encouragement has positive short-term effects on exercise behavior. Highlights: We collected longitudinal data on exercise and social interactions through public access to the Wanbu network. We developed the fixed- and random-effect model to explore short-term effect of social encouragement on exercise with longitudinal data. Our work presented that all three social interactions (comments, thumbs-up, and posts) have positive effects on the next day's exercise level. Our work presented that social encouragement has positive short-term effects on exercise behavior.